Economic distress, financial toxicity, and medical cost‐coping in young adult cancer survivors during the COVID‐19 pandemic: Findings from an online sample. Issue 23 (5th August 2021) - Thom, Bridgette; Benedict, Catherine; Friedman, Danielle N.; Watson, Samantha E.; Zeitler, Michelle S.; Chino, Fumiko
Abstract : Background: Young adult (YA) cancer survivors are at risk for financial toxicity during and after cancer treatment. Financial toxicity has been associated with medical‐related cost‐coping behaviors such as skipping or delaying treatment. The coronavirus disease 2019 (COVID‐19) pandemic has resulted in dire economic consequences that may worsen financial hardship among young survivors. Methods: This was a cross‐sectional survey; data collection occurred online. A convenience sample was recruited through YA cancer advocacy groups and social media. Negative economic events associated with the COVID‐19 pandemic (eg, income loss, increased debt, and decreased job security) and medical‐related cost‐coping were documented. A validated measure assessed cancer‐related financial toxicity. Results: Participants (N = 212) had a mean age of 35.3 years at survey completion and a mean age of 27.4 years at diagnosis. Financial toxicity (mean, 14.0; SD, 9.33) was high. Two‐thirds of the sample experienced at least 1 negative economic event during COVID‐19, and 71% engaged in at least 1 medical cost‐coping behavior. Cost‐coping and pandemic‐related negative economic events were significantly correlated with cancer‐related financial toxicity. In multivariable analyses, pandemic‐related negative economic events and financial toxicity were associated with cost‐coping. Conclusions: Acute negative economic events associated with the COVID‐19 pandemic may exacerbate cancer‐related financial toxicity and overall financial hardship among YAs and lead to cost‐coping behaviors that can compromise survivorship care and health outcomes. Multilevel, systematic interventions are needed to address the financial needs of YA survivors after the global pandemic. Abstract : This study illustrates how the acute negative economic events associated with the coronavirus disease 2019 pandemic may have exacerbated existing cancer‐related financial toxicity and general financial hardship among young adult cancer survivors. These negative economic events and financial toxicity are associated with cost‐coping behaviors that can compromise survivorship care and health outcomes.